Devil on the Stairs : Looking back on the eighties - Storr, Robert; Tannenbaum, Judith; Newport Harbor Art Museum, Newport Beach ([Philadelphia] : Institute of Contemporary Art, University of Pennsylvania, 1991)
Ahearn, John ; Applebroog, Ida ; Artschwager, Richard ; Baldessari, John ; Basquiat, Jean Michel ; Beuys, Joseph ; Bleckner, Ross ; Borofsky, Jonathan ; Bourgeois, Louise ; Clemente, Francesco ; Deacon, Richard ; Fischl, Eric ; Gober, Robert ; Goldin, Nan ; Golub, Leon ; Hammons, David ; Haring, Keith ; Holzer, Jenny ; Immendorff, Jörg ; Kabakov, Ilya ; Kelley, Mike ; Kiefer, Anselm, ; Komar & Melamid ; Koons, Jeff ; Kruger, Barbara ; Lawler, Louise ; Levine, Sherrie ; Levinthal, David ; Marden, Brice ; McCollum, Allan ; Mendieta, Ana ; Murray, Elizabeth ; Piper, Adrian ; Polke, Sigmar ; Puryear, Martin ; Richter, Gerhard ; Rollins, Tim + K.O.S. ; Rothenberg, Susan ; Ryman, Robert ; Salle, David ; Samba, Chéri ; Serrano, Andres ; Sherman, Cindy ; Simmons, Laurie ; Simpson, Lorna ; Spero, Nancy ; Spiegelman, Art ; Wall, Jeff ; The Witness Project ; Wojnarowicz, David
Devil on the Stairs : Looking back on the eighties, Institute of Contemporary Art, Philadelphia, Pennsylvania, October 4, 1991 - January 5, 1992 ; Newport Harbor Art Museum, Newport Beach, California, April 16 - June 21, 1992
boek